Factors influencing students’ preference for green tea at UiTM Cawangan Pulau Pinang / Nur Tahirah Abd Aziz ... [et al.] - Abd Aziz, Nur Tahirah; Rozekh, Nor Azureen; Hussin, Shahril; Zakaria, Nurul’Aishah @ N; Mohd Akhir, Irina (Universiti Teknologi Mara Cawangan Pulau Pinang, 2023)
One of the healthiest coffee beverages, green tea is incredibly refreshing and soothing. Nowadays, the majority of younger consumers see and perceive tea more as a sensual and healthy beverage, which is different from the past. Green tea consumption has many health benefits for students, such as affecting students’ eating patterns and food intake. The purpose of this study is to identify the factors, such as students’ habits, expected health benefits, and sensory attributes, that influence UiTM Cawangan Pulau Pinang students' preferences for green tea. 400 respondents who have experienced and acknowledged the benefits of green tea participated in this study using an online survey. Descriptive, correlational, and multiple regression analyses were used to analyze the data. The results show that students' habits have a strong influence on their preference for green tea, and the results are statistically significant when compared to others. Student habits have a profound impact on their preference for green tea, making it a popular choice worldwide. It was believed that this study would boost green tea marketing, especially in Malaysia. By opting for green tea, students contribute to knowledge generation, enhance their professional applications, and contribute to positive social change. Food operators can tap into the growing popularity of this healthy beverage and stay ahead of the curve in the ever-evolving food industry by incorporating green tea drinks into their menus.